Human blood-labyrinth barrier model to study the effects of cytokines and inflammation - Sekulic, Marijana; Puche, Raoul; Bodmer, Daniel; Petkovic, Vesna (Frontiers in Molecular Neuroscience, 2023)
Hearing loss is one of the 10 leading causes of disability worldwide. No drug therapies are currently available to protect or restore hearing. Inner ear auditory hair cells and the bloodlabyrinth barrier (BLB) are critical for normal hearing, and the BLB between the systemic circulation and stria vascularis is crucial for maintaining cochlear and vestibular homeostasis. BLB defects are associated with inner ear diseases that lead to hearing loss, including vascular malformations, inflammation, and Meniere's disease (MD). Antibodies against proteins in the inner ear and cytokines in the cochlea, including IL-1α, TNF-α, and NF-kβ, are detected in the blood of more than half of MD patients. There is also emerging evidence of inner ear inflammation in some diseases, including MD, progressive sensorineural hearing loss, otosclerosis, and sudden deafness. Here, we examined the effects of TNF-α, IL6, and LPS on human stria vascularis-derived primary endothelial cells cultured together with pericytes in a Transwell system. By measuring trans-endothelial electrical resistance, we found that TNF-α causes the most significant disruption of the endothelial barrier. IL6 had a moderate influence on the barrier, whereas LPS had a minimal impact on barrier integrity. The prominent effect of TNF-α on the barrier was confirmed in the expression of the major junctional genes responsible for forming the tight endothelial monolayer, the decreased expression of ZO1 and OCL. We further tested permeability using 2 µg of daptomycin (1619Da), which does not pass the BLB under normal conditions, by measuring its passage through the barrier by HPLC. Treatment with TNF-α resulted in higher permeability in treated samples compared to controls. LPStreated cells behaved similarly to the untreated cells and did not show differences in permeability compared to control. The endothelial damage caused by TNF-α was confirmed by decreased expression of an essential endothelial proteoglycan, syndecan1. These results allowed us to create an inflammatory environment model that increased BLB permeability in culture and mimicked an inflammatory state within the stria vascularis.